Suspect screening in Mussels cultured in straits of Tebrau leading to public perception and awareness survey on pharmaceuticals and personal care products (PPCPs) - Yong, Zhi Yuan; Chong, Yen San; Mohamad Hanafi, Muhammad Arif Haikal; Abdul Wahab, Mohd Firdaus; Lee, Hooi Ling; Bakar, Mohd Bakri; Abdul Majid, Zaiton; Basar, Norazah; Chandren, Sheela; Hasbullah, Hasrinah; Othman, Mohd Hafiz Dzarfan; Chan, Wei Yee; et al. (American Chemical Society, 2024)
The presence of multidrug-resistant bacteria in Malaysian waters and farmed aquatic species in its estuarine environment suggests contamination due to pharmaceuticals and personal care products (PPCPs). However, this issue has lacked serious attention. This study performed suspect screening to identify tentative PPCPs in water and mussels located at the Melayu River during high and low tides, followed by a public awareness survey to understand the public behavior toward handling PPCPs. In total, 75 PPCPs were tentatively identified. Four and six compounds were found in surface water during low and high tides, respectively, while mussel samples showed 50 compounds during low tide and 35 compounds during high tide. Interestingly, 7 pharmaceuticals and 4 personal care products appeared in both tides in mussel samples. Survey findings revealed that while respondents understood PPCP pathways entering the environment and associated threats, they were unaware of relevant laws and proper disposal methods for unused pharmaceuticals, which are often discarded together with domestic wastes. The findings highlight the urgent need for detailed suspect screening with targeted analysis in order to establish relevant regulatory measures apart from providing public education on the proper disposal of PPCPs to mitigate contamination.